2006
DOI: 10.1186/1471-2199-7-17
|View full text |Cite
|
Sign up to set email alerts
|

Role of transcription factor Sp1 and CpG methylation on the regulation of the human podocalyxin gene promoter

Abstract: Background: Podocalyxin (podxl) is a heavily glycosylated transmembrane protein mainly found on the apical membrane of rat podocytes and also in endothelial, hematopoietic, and tumor cells. Despite of its interest no much is known about the transcriptional regulation of podxl in different cells. Thus, we aimed at studying the functional features of the 5'-regulatory region of the human Podxl gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…6 A ). It has been reported that cytosine methylation may inhibit Sp1 binding to its consensus sites, therefore affecting its positive trans -activity (38, 39). Thus, we asked whether this epigenetic modification might play a role in the modulation of Sp1 binding to the SYN1 promoter.…”
Section: Resultsmentioning
confidence: 99%
“…6 A ). It has been reported that cytosine methylation may inhibit Sp1 binding to its consensus sites, therefore affecting its positive trans -activity (38, 39). Thus, we asked whether this epigenetic modification might play a role in the modulation of Sp1 binding to the SYN1 promoter.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Sp1, which also plays a role in podocyte differentiation [24,25,26], was shown to specifically bind reg3 in EMSA supershift experiments (fig. 4a).…”
Section: Discussionmentioning
confidence: 99%
“…Sp1 is ubiquitously expressed, but notably there are up to 100-fold differences in the levels of Sp1 in different cell types of the developing mouse embryo, which may reflect involvement in cell-specific transcription regulation pathways [24]. A role for this transcription factor in nephrogenesis has been proposed based on data for its spatial and temporal expression in developing glomeruli and its ability to regulate WT1 and podx1 expression [25,26]. …”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found that methylation of SP1 binding sites prevents its binding and subsequent gene activation, while others have shown that methylation of SP1 binding sites does not alter its binding (e.g. Harrington et al, 1988; Holler et al, 1988; Mancini et al, 1999; Butta et al, 2006; Douet et al, 2007). We found that there were no obvious differences in the DNA methylation patterns associated with the SP1 binding sites between the Pit-1/0 cell lines, which do not express the Lhx3 gene and the Pit-1/Triple cell line that does express the Lhx3 gene.…”
Section: Discussionmentioning
confidence: 99%